POTENSI HIKING TRAIL LUAK GADANG BUKIK BAKA MENJADI DAYA TARIK WISATA DI JORONG GUGUAK RANGPISANG NAGARI KAMANG HILIA KABUPATEN AGAM - Rozi Yuliani (JURNAL STAMINA, 2018)
Sport Tourism has the potential to improve the involvement of community to increase the global competitiveness. Sport Tourism is tourism activities combined with sports activities, or exercising while traveling or vice versa. The improvement of Indonesian tourism image also involved the community based on tourism. The aim of this research is to develop Luak Gadang Bukik Baka to be a sport tourism in scope hiking, camping and water park. That type of sport is one of the popular tourism sports. The method of this research is qualitative descriptive, for the informen, researcher use snowball techniques. Data collection techniques are used by means of observation, interviews and documentation. Based on the result of the research, it can be concluded that the development has developed in the aspect of activities and facilities in the form of hospitality and facilities. While the physical aspects, aspects of attractiveness, aspects of accessibility, and socio-economic and cultural aspects of Luak Gadang Bukik Baka have not yet developed as well. Kabupaten Agam government is expected to give the best services for the tourist, the community of Jorong Guguak Rangpisang in developing Luak Gadang Bukik Baka to become a tourist object that is worth visiting by tourist.